PENGARUH MEDIA PEMBELAJARAN FILM KARTUN TERHADAP KEMAMPUAN BERBICARA DALAM MENCERITAKAN KEGEMARAN SISWA DI KELAS II SDN 1 SUKAMULYA - Ajeng Sinta Wati; Dessy Wardiah; Aldora Pratama (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The Influence Of Cartoon Learning Media To Improve The Ability To Tell Student' Hobbie In Grade II SDN 1 Sukamulya. The purpose of this study was to determine the influence of cartoon ffilm media to improve speaking skills in telling students' hobbies in grade II SDN 1 Sukamulya. This research uses the One Group Pretest Design method – Posstest Design. The unit of analysis in this study is the cartoon film "The Samson Family and the Fahriani Family". The sampling technique in this study is by Purposive Sampling. Data was collected using observation instruments, documentation and tests. The data was analyzed using the N-Gain Score (Normailized Gain) formula. It can be seen that the use of cartoon film media and the speaking ability of students in grade II SDN 1 Sukamulya has an effect in accordance with expectations. Through this cartoon film media, students are able to improve their speaking skills in telling students' hobbies. Keywords: cartoon film media, speaking ability